Analysis of precompetitive preparation of the elite rowers towards European championship - Petkus, E.; Dadeliene, R.; Raslanas, A. (LASE Journal of Sport Science, 2013)
The goal of the research was to analyze the content of double scull elite rowers` pre-competition mezocycle and to assess the efficiency of aerobic capacity training. The training content of European champions of double scull during pre-competition mezocycle was analyzed. The mezocycle was composed of four microcycles: introductory microcycle of aerobic and creatine-phosphate power and endurance training, microcycle of aerobic critical power, endurance training, and pre-competition parts. In the introductory part, the intensity of aerobic training work was very close to anaerobic threshold limit (ATL), i.e. La=2-3mmol/l and combined with muscle mass training exercises. In the second microcycle, aerobic training intensity was at ATL±5%, La=3-6mmol/l and combined with creatine-phosphate power training exercises. In the third microcycle, work intensity between ATL and critical intensity limit (CIL), La=4-9mmol/l, was dominating. In the fourth pre-competition microcycle, working volume was reduced by 30% with different intensity, La=3-14mmol/l, and with improvement of rowing pace from start and technique. Researches were performed with gas analyzer "Oxycon Mobile" and concept "Concept 2". We have revealed that aerobic capacity was growing during study period. VO2max in athlete M. was growing from 62.3 up to 65.3ml/min/kg, in athlete R. - from 61.3 up to 65.2ml/min/kg. This research of ours has revealed that elite rowers, during pre-competition mesocycle when working close to ATL and between ATL and CIL and less working on glycolytic zone, have significantly increased their aerobic capacity that compose approximately 80% of sport performance.